2006
DOI: 10.1590/s1415-52732006000400003
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da L-Glutamina sobre o perfil leucocitário e a função fagocítica de macrófagos de ratos estressados

Abstract: ObjetivoVerificar o efeito da administração intraperitoneal de glutamina, prévia a uma situação de estresse, sobre o número de leucócitos do sangue e sobre a taxa de fagocitose de macrófagos alveolares de ratos. MétodosRatos machos Wistar aos 90 dias de idade foram divididos em controle (C, n=15), estresse (C+E, n=16), glutamina (GLN, n=15) e glutamina e estresse (GLN+E, n=15) e mantidos em condições padronizadas. Os grupos GLN e GLN+E receberam, via intraperitoneal (v ip), L-glutamina (0,2g/kg de peso corpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
6
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 23 publications
3
6
0
6
Order By: Relevance
“…The proportion of lymphocytes in the whole blood for the saline group was higher than neutrophils. This result is according to other experiments conducted in Wistar rats and mice, for the mentioned populations and for the other analyzed populations: monocytes and eosinophils (Crockett et al, 2004;Kreimer et al, 2005;Lagasse & Weissman, 1996;Leandro et al, 2006). All the groups that received thioglycollate stimulus presented a higher proportion of neutrophils in the whole blood when compared with the saline group, which correlates with the inflammatory state of the rat (Lagasse & Weissman, 1996).…”
Section: Discussionsupporting
confidence: 83%
“…The proportion of lymphocytes in the whole blood for the saline group was higher than neutrophils. This result is according to other experiments conducted in Wistar rats and mice, for the mentioned populations and for the other analyzed populations: monocytes and eosinophils (Crockett et al, 2004;Kreimer et al, 2005;Lagasse & Weissman, 1996;Leandro et al, 2006). All the groups that received thioglycollate stimulus presented a higher proportion of neutrophils in the whole blood when compared with the saline group, which correlates with the inflammatory state of the rat (Lagasse & Weissman, 1996).…”
Section: Discussionsupporting
confidence: 83%
“…(32) There are some studies (5) in animals and humans that demonstrate that stress reduces the total leukocyte count, thus corroborating our results.…”
Section: Discussionsupporting
confidence: 89%
“…Many studies demonstrate that stress and emotional reactions affect the immune system. ( 4 , 5 ) The most common way to identify possible alterations in the immunological system is by complete blood counts, including the hematopoietic system, leukocyte profile or biochemical markers of stress. ( 4 , 5 ) Some works ( 5 , 6 ) have demonstrated that even before the feedback system, characterized by a constant turnover of cells, which need constant replication to maintain the leukocyte, platelet and erythrocyte populations, stress can affect the number and quality of these cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have demonstrated that stress affects the immune 2 , 3 and nervous systems with regard to the cognitive functions 4 including that of attention. 5 Since 1980, behavior tests have been developed to evaluate attention and investigate the nervous circuits related to these processes.…”
mentioning
confidence: 99%